2006
DOI: 10.1016/j.jsat.2005.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to violence among substance-dependent pregnant women and their children

Abstract: This study examined the prevalence of exposure to violence among drug-dependent pregnant women attending a multidisciplinary perinatal substance abuse treatment program. Participants (N = 715) completed the Violence Exposure Questionnaire within 7 days after their admission to the program. Their rates of lifetime abuse ranged from 72.7% for physical abuse to 71.3% for emotional abuse to 44.5% for sexual abuse. Their rates of abuse remained high during their current pregnancy, ranging from 40.9% for emotional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 44 publications
0
27
1
5
Order By: Relevance
“…Examples include poor nutrition, inadequate medical care, poverty, chronic medical problems (eg, HIV infection, asthma), and domestic violence [20,21]. Many of these variables are associated with adverse maternal and infant outcomes, even in the absence of maternal cocaine use.…”
Section: Co-occurring Environmental Risk Factorsmentioning
confidence: 99%
“…Examples include poor nutrition, inadequate medical care, poverty, chronic medical problems (eg, HIV infection, asthma), and domestic violence [20,21]. Many of these variables are associated with adverse maternal and infant outcomes, even in the absence of maternal cocaine use.…”
Section: Co-occurring Environmental Risk Factorsmentioning
confidence: 99%
“…In one study, more than 75% of patients in SUD treatment reported perpetrating violence toward others . Yet, despite evidence of the large scope of this problem, the A wealth of research links prior violent victimization to the development of SUDs (Chermack, Stoltenberg, et al, 2000;Easton, Swan, & Sinha, 2000;Farley, Golding, Young, Mulligan, & Minkoff, 2004;Velez et al, 2006). Studies also suggest that exposure to violence may impact the severity and course of SUD.…”
Section: Introductionmentioning
confidence: 99%
“…While psychotherapy, pharmacotherapy, or a combination of the two have all been recommended to treat psychopathology,32, 33 the long-term effects of psychopharmacological treatments on neonatal outcomes remain unclear,34 therefore, integrating nonpharmacologic interventions for treating depression35 or anxiety, such as group therapy, may be most optimal interventions depending upon each woman’s psychological condition and symptom severity. However, at the same time, other serious issues affecting women’s mental health and risk for HIV and other infectious diseases including homelessness3 and violence2 also need to be addressed in order to truly improve the health and functioning of this population of women.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, amidst the array of psychosocial and legal challenges facing the treatment of drug dependent pregnant women,1, 2, 4, 1416 the potentially considerable significance of comorbid psychiatric disorder status in relation to infectious disease risk behavior in this population has heretofore not been addressed. To the extent that pregnant women with opioid and cocaine dependence exhibit elevated rates of HIV and other infectious disease risk behavior by virtue of undetected and untreated psychiatric comorbidities, the health of both women and their fetuses are probably greatly compromised.…”
Section: Introductionmentioning
confidence: 99%